2021
DOI: 10.3390/nu13092943
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated Isoflavonoids-Rich Extract of Erythrinae Cortex Exerted Bone Protective Effects by Modulating Gut Microbial Compositions and Metabolites in Ovariectomized Rats

Abstract: Flavonoids, found in a wide variety of foods and plants, are considered to play an important role in the prevention and treatment of osteoporosis. Our previous studies demonstrated that Erythrina cortex extract (EC) rich in prenylated isoflavonoids exerted bone protective effects in ovariectomized (OVX) rats. The present study aimed to investigate the interactions of gut microbiota with the EC extract to explore the underlying mechanisms involved in its beneficial effects on bone. Sprague-Dawley female rats of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 47 publications
1
6
1
Order By: Relevance
“…These findings indicate that the OVX group experienced an acceleration in bone tissue and bone metabolism, consistent with previous research. 35,36 The consumption of quinoa resulted in a partial reduction in ALP levels, indicating its potential significance in regulating the equilibrium between bone formation and bone resorption. CTX-I is a type I collagen fragment produced during bone maturation, which can sensitively reflect the activity of osteoclasts and is considered as a specific indicator of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the OVX group experienced an acceleration in bone tissue and bone metabolism, consistent with previous research. 35,36 The consumption of quinoa resulted in a partial reduction in ALP levels, indicating its potential significance in regulating the equilibrium between bone formation and bone resorption. CTX-I is a type I collagen fragment produced during bone maturation, which can sensitively reflect the activity of osteoclasts and is considered as a specific indicator of bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have noted that the antiosteoporotic effects of isoflavonoids are mediated through modulation of bone turnover and improvement of bone microarchitecture (Zhang et al, 2010;Tousen et al, 2016;Lambert et al, 2017). Similarly, a study by Xiao et al indicated that the skeletal protective effect of isoflavonoids-rich extract of Erythrina cortex was associated with alterations in several specific gut bacteria (restoration of Ruminiclostridium and inhibition of Alistipes and Akkermansia) and an increase in SCFAs (Xiao et al, 2021). Cinnamic acid is a natural compound found in dietary plants and has a variety of biological properties.…”
Section: Natural Substancesmentioning
confidence: 99%
“…Similarly, a study by Xiao et al. indicated that the skeletal protective effect of isoflavonoids-rich extract of Erythrina cortex was associated with alterations in several specific gut bacteria (restoration of Ruminiclostridium and inhibition of Alistipes and Akkermansia) and an increase in SCFAs ( Xiao et al., 2021 ). Cinnamic acid is a natural compound found in dietary plants and has a variety of biological properties.…”
Section: Interventions With Specific Gut Microbiota To Improve Bone H...mentioning
confidence: 99%
“…Sprague-Dawley rats (female, 3 months old, 200-220 g) were purchased from Hubei Experimental Animal Research Center (Wuhan, China). After a 1-week acclimation period, the animals underwent either bilateral laparotomy (Sham group, n = 10) or bilateral ovariectomy (OVX group, n = 30) as previously described (Xiao et al, 2021). Then the OVX animals were randomly divided into 3 groups of 10 rats in each group: OVX control, OVX with low dose AETC (6.0 g raw materials/kg)-treated group and high dose AETC (12.0 g raw materials/kg)-treated group.…”
Section: Animal Model and Treatment Protocolmentioning
confidence: 99%